Socio-community neuroeducation: towards the ideal society latin american - Peña Peinado, Raquel Del Valle (Conexiones UG, 2024)
The human brain has the capacity to capture and/or retain, just as in a movie, everything that the individual contemplates in his or her daily life. The ultimate goal of this reflexive argumentative article is to unravel how the thinking being within the great social spiral manages to coexist, and at the same time resignify its customs in the context in which it develops. It is based on a methodology with a transmethodical approach to systematize the information collected. The methods used: longitudinal study, as well as the documentary analysis of literature on the subject, reflexive hermeneutics, and systematization of experiences with an anecdotal record, through the technique of participant observation for 12 years, finding the absence of values, lack of family awareness, and that the family is the fundamental cell of society. Reflecting that, society has its way of learning, from its customs, set of values or popular wisdom nourishes its social brain, so it is these premises that contribute to go towards the ideal society through a transdisciplinary approach that allows the understanding of social behavior, so a new construct for the social sciences is provided: Socio-Community Neuroeducation.